STRATEGI GURU ASRAMA DALAM PEMBINAAN KETERAMPILAN MEMBACA AL-QUR’AN SANTRI KELAS V DAN VI MADRASAH IBTIDAIYAH DI MA’HAD AL-ZAYTUN - Nur Jihan, Adilla; Humaeroh, Iis; Nopasari, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read the Qur’an is a fundamental competency that students must possess in Islamic education. However, there are still students who are unable to read the Qur’an optimally, whether in terms of fluency, articulation of letters, or the application of tajwid. This study aims to describe the Qur’an reading skills of fifth- and sixth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun and to analyze the strategies used by boarding school teachers in developing these skills. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving one dormitory supervisor, two dormitory teachers, and eight students selected through purposive sampling. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, with validity testing using source and technique triangulation. The results of the study show that of the 164 fifth-grade students, 90 were fluent in reading the Qur’an and 74 were not yet fluent. Meanwhile, of the 176 sixth-grade students, 131 were fluent in reading and 45 were not yet fluent. The strategies implemented by the boarding school teachers included forming study groups based on students’ dorm rooms, establishing the habit of reading the Qur’an after Maghrib prayer, conducting periodic reading assessments, and applying the Iqro’, Murajaah, and Talaqqi methods. These strategies were proven to help improve students’ Qur’an reading skills gradually. This study underscores the importance of the role of boarding school teachers in fostering a sustainable Quranic learning environment within boarding schools.